Q: What is the answer to x-2 equals 3x plus 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x2 + 3x + 7 = 5 ∴ x2 + 3x + 2 = 0 ∴ (x + 1)(x + 2) = 0 ∴ x ∈ {-2, -1}

3x-1 = 11 3x = 11+1 3x = 12 x = 4 Therefore: x2+2 = 18

- If 3X - 1 = 11, what is the value of X^2 + X?

x2 + 3x + 3 = 7Subtract 7 from each side:x2 + 3x - 4 = 0Factor the left side:(x + 4) (x - 1) = 0x = - 4x = +1

x2 + 3px + p = 0 x2 + p(3x + 1) = 0 p(3x+1) = -x2 p = -x2/(3x+1) So p can have any value at all. In fact, around x = -1/3, p goes asymptotically to + and - infinity.

Related questions

x2 + 3x + 7 = 5 ∴ x2 + 3x + 2 = 0 ∴ (x + 1)(x + 2) = 0 ∴ x ∈ {-2, -1}

3x-1 = 11 3x = 11+1 3x = 12 x = 4 Therefore: x2+2 = 18

- If 3X - 1 = 11, what is the value of X^2 + X?

1 and 2

x=-11

x2 + 3x + 3 = 7Subtract 7 from each side:x2 + 3x - 4 = 0Factor the left side:(x + 4) (x - 1) = 0x = - 4x = +1

x2 + 3px + p = 0 x2 + p(3x + 1) = 0 p(3x+1) = -x2 p = -x2/(3x+1) So p can have any value at all. In fact, around x = -1/3, p goes asymptotically to + and - infinity.

3x-1 = 11 3x = 11+1 = 12 x = 12/3 = 4 Therefore: x2 + 2 = 16 + 2 = 18

3x-1=11 3x = 12 x = 4 Then, x^2 +x = 20.

x3+3x2+3x+2 divided by x+2 equals x2+x+1

x2+3x+1 = 0 Using the quadratic equation formula gives you: (x+2.618033989)(x+0.3819660113) = 0 So: x = -2.618033989 or x = -0.3819660113

3x-1=11 solves to x=4. Plug in 4 to get 42+4. The answer is 20.